PENGARUH YEAR END EFFECT TERHADAP PERUSAHAAN MANUFAKTUR SEKTOR ANEKA INDUSTRI PERIODE TAHUN 2010-2014 - Berniz, Yulis Maulida (PERMANA, 2015)
New year is year where there is tradisional by the appearance of new spirit with new resolution. It affect to physicology of the investors factor / stock exchange decision taker to thereinvestment, where it cause to the fluctuate share value in Indonesian Stock Exchange. This researchs aim is to analyse is there any pattern system to waras effect January and there are difference return abnormal average 3(three) days before and after effect january. The Share that become a research sample is share from the manufacture company in the sector part of various listed industriesin BEI in 2010-2014.Â The research method which is being used to analyse whether there is a system pattern toward effect Jakarta an whether there any significant difference between return abnormal average before and after effect January by using normality test, descriptive, statistic and pairead samples test the outcome of the first hipotesis is the nonexistence of the pattern toward effect January to the return mean - adjusted model. The second hypotesis outcome is there is No significant difference between return abnormal average before and after effect January by using return mean adjusted modelKata kunci : January Effect, dan Abnormal Return.